2004
DOI: 10.1101/gr.2242604
|View full text |Cite
|
Sign up to set email alerts
|

Regulog Analysis: Detection of Conserved Regulatory Networks Across Bacteria: Application to Staphylococcus aureus

Abstract: A transcriptional regulatory network encompasses sets of genes (regulons) whose expression states are directly altered in response to an activating signal, mediated by trans-acting regulatory proteins and cis-acting regulatory sequences. Enumeration of these network components is an essential step toward the creation of a framework for systems-based analysis of biological processes. Profile-based methods for the detection of cis-regulatory elements are often applied to predict regulon members, but they suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 58 publications
(57 reference statements)
3
67
1
Order By: Relevance
“…This is particulary important for the interspecies transfer of gene regulatory networks (Babu et al, 2006;Baumbach, 2010) but also for the scanning of new regulon members (Pérez et al, 2007). The utilization of pattern matching methods in combination with phylogenetic conservation is also called regulog analysis (Alkema et al, 2004). During a regulog analysis the relativ conservation score RCS is defined by the fraction of orthologs, that share the same potential TFBS.…”
Section: Positional Preference Of Tfbssmentioning
confidence: 99%
“…This is particulary important for the interspecies transfer of gene regulatory networks (Babu et al, 2006;Baumbach, 2010) but also for the scanning of new regulon members (Pérez et al, 2007). The utilization of pattern matching methods in combination with phylogenetic conservation is also called regulog analysis (Alkema et al, 2004). During a regulog analysis the relativ conservation score RCS is defined by the fraction of orthologs, that share the same potential TFBS.…”
Section: Positional Preference Of Tfbssmentioning
confidence: 99%
“…This rewiring has been compared to changing the "software" of the transcriptional regulation machinery [20], as opposed to changing the "hardware". The latter would mean changing the set of TFs or regulated genes -a process observed by Babu et al [7] and Lozada-Chavez et al [16] -between phylogenetically distant organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Both works showed that the set of regulatory genes -even global transcription factors -clearly varies from one group of organisms to another. On the other hand, several studies have shown that, within a group of closely related organisms, the conservation of a TF and a subset of the structural genes it regulates are not sufficient to assume that regulatory links between them are conserved between such two organisms [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain a better understanding of the transcriptional regulatory network in other organisms, computational methods to extrapolate this information from model organisms to poorly studied organisms by exploiting the wealth of information in the form of publicly available completely sequenced genomes have been developed [18][19][20][21][22][23][24][25][26][27][28][29]. Such methods can be broadly grouped into two classes: (i) Orthology based methods: This approach exploits the basic principle that orthologous transcription factors regulate orthologous target genes in the different genomes.…”
mentioning
confidence: 99%